Assessing the effectiveness of botulinum toxin injections into masticatory muscles in the treatment of temporomandibular disorders - Kahn Alexis; Bertin Helios; Corre Pierre; Praud Morgan; Paré Arnaud; Kün-Darboi (EDP Sciences, 2018)
Introduction: Temporomandibular disorders (TMD) are a common and invalidating disease sometimes difficult to treat. Current international recommendations favour reversible and non-invasive treatments, including the injection of botulinum toxin (BTX) into masticatory muscles. There is no strong evidence of its effectiveness. Objective: The main goal of this study was to assess the effectiveness of BTX six months following injection, in terms of pain, mouth opening, improvement of symptoms and duration of effect. Materials and methods: A retrospective study carried out at Nantes University Hospital between 2014 and 2016. Results: Thirty-four patients were included. The mean age was 37 years (17-76) and seventy six percents were female. Eighty percent of patients reported a significant improvement, notably in cases of arthralgia, which decreased in 8/18 (44%) patients (p < 0.05). The mean duration of measured efficacy was 4.2 months. Discussion: Significant improvement in cases of arthralgia and a tendency for improvement in cases of myalgia, with a mean duration of action of 4.2 months. Although BTX injection do not guarantee complete resolution of myofascial pain, it have been shown to have beneficial effects on some symptoms have been shown. Conclusion: Botulinum toxin should be considered as an alternative treatment when other conservative methods fail to yield satisfactory results. A thorough multicentre assessment is necessary in the future to scientifically validate its use.